Considerations in Using Artificial Intelligence to Simulate Orthodontic Treatment for Implant-Prosthetic Purposes - Amelia Smaranda Roșianu; Sanda Mihaela Popescu; Daniel Adrian Târtea; Stelian Mihai Sever Petrescu; Răzvan Mercuț; Marina Olimpia Amărăscu; Mihaela Ionescu; Ionuț Cristian Reşceanu; Alin Gabriel Ionescu (Journal of Clinical Medicine, 2026)
Background/Objectives: Orthodontic treatment planning software with artificial intelligence has been introduced into practice in recent years. They allow the simulation of the results of orthodontic treatment in several scenarios. The aim of the study was to compare the results of a simulated preimplantation orthodontic treatment plan in cases of oral rehabilitation between two software, with three different setups and their evaluation by an orthodontist. Methods: The in silico study included 10 cases of digital models obtained by intraoral scanning from patients with reduced lateral edentulousness who required implant-prosthetic treatment. The following software were used for the simulations: Medit Ortho Simulation v1.4.1 and Diorco dentOne v1.6.6.9 in two variants (Autoalign and a variant with fixation of the teeth bordering the edentulous breach). For comparison, the analysis of the Bolton report and of the movements in the three plans proposed by the software were used. Results: The results of the study showed that there were statistically significant differences between the simulations proposed by the two software tools. The evaluation made by the orthodontist showed that the Medit Ortho Simulation software was closer to the goal visualized by the orthodontist. Conclusions: The differences in movement between the simulations influenced the assessments of occlusions, tooth stability, and overall treatment planning that depend on the accuracy of vertical measurements.